New records for the caddisfly fauna of Slovenia (Insecta: Trichoptera) - Urbanič, Gorazd (Acta entomologica slovenica (Ljubljana), 2000)
The list of nine new records for Slovenian caddisfly fauna from the valley of the river Ščavnica is given. Adult caddisfilies were caught using a sweeping net and a light-trap, whereas larvae were sorted from the benthic samples. Five species were identified in adult and larval stages while four species were identified only in the larval or adult stage. The number of recorded Slovenian Trichoptera species increased up to 216.
Keywords: Ecosystem; Insects; insekti; mladoletnice; Slovenia; Slovenija; Ščavnica; zoologija; zoology